Legal Protection Efforts for Micro, Small and Medium Enterprises Against Unfair Business Competition - Elsita Lumban Gaol; July Esther; Ria Juliana Siregar (PT FORMOSA CENDEKIA GLOBAL, 2025)
The focus of this study is the efforts made by the law to protect micro, small, and medium enterprises (MSMEs) from unfair competition. This law is regulated through Law No. 5 of 1999. Activities prohibited in business competition are the topic of this study. This study investigates the impact of unfair business competition on MSME actors, which makes the KPPU necessary to supervise business competition. The results of the study indicate that legal protection for MSMEs against unfair business competition practices is very important because these practices can affect the growth and desires of MSMEs. This finding provides insight for the government, business actors, and legal experts. The government can establish stricter laws to supervise business competition. To avoid unfair business practic